The Influence of an Islamic Values-Base Father Training Program on the Social Skills of Preschool Children - Prima, Ellen (Journal of Educational, Health and Community Psychology, 2025)
The active involvement of fathers in child-rearing has a positive impact on a child’s developmental process, including their future mental health. The aim of this study was to examine the influence of a Father Training Program on the social skills of preschool children. The study was conducted in two preschools in Purwokerto using a pretest-posttest control group experimental design. Both the experimental and control groups consisted of 40 preschool children, with their fathers from different preschools. The Father Training Program was implemented over a period of twelve weeks solely for the fathers in the experimental group, while the control group did not receive any training. Data on children’s social skills were gathered by preschool teachers before and after the implementation of the Father Training Program using the Social Skills Assessment Scale (SSAS). The data were analyzed using one-factor covariance analysis (ANCOVA) and t-tests. The results indicated a statistically significant difference between the control and experimental groups in terms of the children’s social skills (p < 0.01); however, the difference between the post-test and retention test mean scores within the experimental group was not significant, suggesting that the effects of the Father Training Program were sustained over time. This finding confirms that training programs, including those focusing on fatherhood, exert a positive influence on children’s social competencies